Will a moral follower please stand up (to the Machiavellian leader)?: the effects of Machiavellian leadership on moral anger and whistleblowing - Lee-Kugler, Taran (Journal of business ethics, 2025)
Machiavellianism is a double-edged sword in leadership. While Machiavellian leaders can be successful, they also can be amoral, influencing their followers to exhibit unethical, counterproductive, and corrupt behaviors. The extant research surrounding Machiavellian leadership has focused narrowly on how followers tacitly endorse such leader behaviors rather than standing up to the leader through whistleblowing. Drawing upon affective events theory (AET), this research examines the relationship between a leader’s Machiavellian traits, followers’ moral anger and empathic concern, and the likelihood of whistleblowing. We conducted three complementary studies that examine our model. First, in a time-lagged, leader-follower field study, we examined the indirect relationship between Machiavellian leadership and whistleblowing through follower moral anger. Then, we adopted the causal chain design and conducted two independent recall experiments using the critical incident technique to establish the moderating role of follower empathetic concern on the causal relationship between Machiavellian leadership and moral anger, and the causal relationship between moral anger and whistleblowing. This research contributes to the literature by highlighting the emotional dynamics that explain a constructive follower response to leader Machiavellianism.